Replication of the Climbing Post on Mount Arjuno Using Augmented Reality (AR) with the Open Asset Import Library Method: Replikasi Pos Pendakian Di Gunung Arjuno Menggunakan Augmented Reality (AR) Dengan Metode Open Asset Import Library - Fachruddin, Muhammad; Dijaya, Rohman; Rosid, Mochamad Alfan (Procedia of Engineering and Life Science, 2023)
Mount Arjuno is a 3,339meter high cone-shaped volcano located in East Java, Indonesia. At this time, information about climbers that is spread in online media makes it easy, there are many features that can be used to find climbing information on Mount Arjuno. Making this Arjuno augmented reality application uses the Rapid Application Development model with the main goal of producing high quality and quantity. Where this method places more emphasis on working on application software and user feedback in the planner. And testing for the tracking distance of the camera to the marker, to ensure the distance that can be traveled by the camera when scanning objects to targets. By creating an android application that uses the Marker Based Tracking method which can assist climbers in choosing hiking trails on Mount Arjuno so that climbers know the distance of the path traveled when climbing.